Efektivitas Latihan Intradialitik pada Hemodialisis - Ratu Izza Auwah Mairo (Journal of Telenursing (JOTING), 2022)
This study aims to systematically review several works of literature that discuss the impact of training or physical activity of Chronic Kidney Disease (CKD) patients undergoing hemodialysis on all factors that can improve the quality of life of CKD patients. The method used is a systematic review by browsing the literature on indexed electronic databases (Scopus, ScienceDirect, CINAHL, Pubmed, Oxford and SAGE). The results showed that the selection of appropriate and safe intradialytic exercises for patients was able to increase physical activity and sleep quality, leg muscle mass, stimulate bone alkaline phosphatase, which can prevent bone loss, lower blood pressure, improve respiratory function and functional capacity, improve physical function, reduce inflammation, improve nutrition, increase bone mineral density, improve exercise tolerance, increase Kt/V and increase the excretion of serum creatinine, blood urea and serum potassium phosphorus. In conclusion, intradialytic exercise during HD will improve the quality of life, decreasing morbidity and mortality of CKD patients undergoing HD. Keywords: Hemodialysis, Intradialytic, Exercise